2023
DOI: 10.36941/ajis-2023-0018
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Mediation Barriers to Self-Efficacy in Improving Hospital Revisitation: Empirical Evidence in the Healthcare Industry in Indonesia

Abstract: This research aims to determine the role of barriers to self-efficacy as mediation on the repeat visits by patients in the National Health Insurance (JKN) at Advanced Referral Health Facilities (FKRTL) Class C in Indonesia. This is an explanatory causality research with the purposive sampling method used to collect data from a cross-sectional survey of 225 patients of class C FKRLT in Jakarta, Bogor, Depok, and Bekasi using a questionnaire. The data collected were analyzed using structural equation modelling (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 61 publications
0
1
0
Order By: Relevance
“…According to ACCA [2020], out of the 53% of auditors who experienced pressure in completing audits, 36% were unable to meet reporting deadlines, and 27% experienced audit risk with going concern issues. This is a professional demand that creates tension [Herda and Lavelle, 2012;Adhikara, et al, 2017;Anwar, et al, 2021;Adhikara, et al, 2022;Andry, et al, 2023], resulting in high employee turnover at KAP [Fogarty and Uliss, 2000]. Studies have also shown that more than one in two audit assistants in the United States quit their jobs after three years of employment [Hiltebeitel and Leauby, 2001], and the statistics published by Swedish Inspectorate of Auditors [2021] revealed a steadily declining number of authorized auditors in Sweden.…”
Section: Introductionmentioning
confidence: 99%
“…According to ACCA [2020], out of the 53% of auditors who experienced pressure in completing audits, 36% were unable to meet reporting deadlines, and 27% experienced audit risk with going concern issues. This is a professional demand that creates tension [Herda and Lavelle, 2012;Adhikara, et al, 2017;Anwar, et al, 2021;Adhikara, et al, 2022;Andry, et al, 2023], resulting in high employee turnover at KAP [Fogarty and Uliss, 2000]. Studies have also shown that more than one in two audit assistants in the United States quit their jobs after three years of employment [Hiltebeitel and Leauby, 2001], and the statistics published by Swedish Inspectorate of Auditors [2021] revealed a steadily declining number of authorized auditors in Sweden.…”
Section: Introductionmentioning
confidence: 99%